Pembelajaran Menyanyikan Lagu Daerah Menggunakan Metode Drill pada Siswa Kelas VII SMP Negeri Muara Kulam - Saipi, Muhammad; Firmansyah, Feri; Firmansyah, Dedy (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Singing folk songs in unison or individually folk songs is still low, especially for subjects that lead to performance practices, this is seen from the minimum completeness criteria because there is still a lack of knowledge about tonic intonation and articulation. This research is to find out whether learning to sing folk songs using the drill method can improve the learning outcomes of class VII students of SMPN Muara Kulam. The method used in this study is a qualitative description of the data sources used areclass VII students and Mrs. Dian Permata Sari, S. Pd as a teacher of SMP Negeri Muara Kulam, themethod used in this learning is the drill method of data collection techniques in this study, namelyobservation, interviews and documentation based on the data analyzed which was carried out in theconclusion that learning to sing folk songs using the method drill on class VII students of SMP Negeri Muara Kulam can improve student learning outcomes can be seen from the value before using the drill method and after using the drill method before using the drill method subject the number of students in class VII is 29